Examining Facebook Groups Engaging in Reading Experiences: The Interactive Therapeutic Process Perspective. (January 2023) - Gazit, Tali; Mass, Hadar; Bronstein, Jenny
Recent years have witnessed a growth in women's reading clubs on social media platforms such as Facebook. Using the theoretical framework of Interactive Therapeutic Process, this study examines the different roles these groups play as platforms for serious leisure fostering socialization, self-expression, a deep engagement with literature, and mutual support between members. A qualitative research method using semi-structured in-depth interviews was employed to examine the thoughts and feelings of twenty women actively participating in two large Facebook reading groups. The findings show that the four stages of the Interactive Therapeutic Process – identification, projection, catharsis, and insight – occur on social media platforms. The thematic analysis of the interviews revealed a fifth and new category of "communality." This category, unique to Facebook groups, emphasizes the importance of a sense of belonging, which evokes a desire to share and receive support within the virtual group. The five stages appeared in three main information activities: reading, writing, and sharing. These findings contribute to the literature by providing a new perspective on online reading groups and the value they provide to their members. Sharing reading experiences online allows the members to cope with the different emotions evoked by reading and offers support in a safe and supportive environment.